2021
DOI: 10.48550/arxiv.2108.12497
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New Constraints on Anisotropic Expansion from Supernovae Type Ia

W. Rahman,
R. Trotta,
S. S. Boruah
et al.

Abstract: We re-examine the contentious question of constraints on anisotropic expansion from Type Ia supernovae (SNIa) in the light of a novel determination of peculiar velocities, which are crucial to test isotropy with SNe out to distances ∼ < 200/ℎ Mpc. We re-analyze the Joint Light-Curve Analysis (JLA) Supernovae (SNe) data, improving on previous treatments of peculiar velocity corrections and their uncertainties (both statistical and systematic) by adopting state-of-the-art flow models constrained independently vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 78 publications
(132 reference statements)
2
9
0
Order By: Relevance
“…for 𝐻 0 in Peterson et al 2021). In addition, Rahman et al (2021) used an improved flow model to correct for PVs and found no evidence for departures from isotropy once the PV corrections were applied, consistent with our findings. The theoretical framework developed by Heinesen (2020) in principle allows us to account for anisotropic expansion of space and to infer peculiar velocities around a background model for both the observer and the sources.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…for 𝐻 0 in Peterson et al 2021). In addition, Rahman et al (2021) used an improved flow model to correct for PVs and found no evidence for departures from isotropy once the PV corrections were applied, consistent with our findings. The theoretical framework developed by Heinesen (2020) in principle allows us to account for anisotropic expansion of space and to infer peculiar velocities around a background model for both the observer and the sources.…”
Section: Discussionsupporting
confidence: 86%
“…We find that the cosmological parameters, 𝑞 𝑚 , 𝑞 𝑑 are uncorrelated with the SN Ia standardisation parameters, using a Pearson 𝑟 test and finding |𝑟 | values < 0.1. A similar correlation between the nuisance parameters and anisotropic cosmologies for the JLA compilation is presented in Dam et al (2017); Rahman et al (2021).…”
Section: Data Availabilitysupporting
confidence: 69%
See 1 more Smart Citation
“…Differences in the treatment of SNIa redshifts have even spilled over into a debate on the evidence for dark energy[1674][1675][1676].…”
mentioning
confidence: 99%
“…These results have been confirmed by analyses relying on different methods and data [23][24][25][26][27][28], although some authors have claimed the absence of such homogeneity scale [29][30][31], arguing that these measurements could be biased by the survey window function [32]. Moreover, some tests of cosmic isotropy revealed potential hints at FLRW breakdown [33][34][35][36][37][38][39][40], albeit disputed by [41][42][43][44][45][46][47]. In light of these results, it is crucial to perform new tests of the CP in order to determine whether it constitutes a valid physical assumption.…”
Section: Introductionmentioning
confidence: 86%